Does increasing pressure always accelerate the condensed material decay initiated through bimolecular reactions? A case of the thermal decomposition of TKX-50 at high pressures. Issue 34 (21st August 2017) - Lu, Zhipeng; Zeng, Qun; Xue, Xianggui; Zhang, Zengming; Nie, Fude; Zhang, Chaoyang
Abstract : Increasing compression causes much more significant H δ + ⋯H δ + repulsion and then more difficult intermolecular H-transfer and increased thermal stability of TKX-50. Abstract : Performances and behaviors under high temperature–high pressure conditions are fundamentals for many materials. We study in the present work the pressure effect on the thermal decomposition of a new energetic ionic salt (EIS), TKX-50, by confining samples in a diamond anvil cell, using Raman spectroscopy measurements and ab initio simulations. As a result, we find a quadratic increase in decomposition temperature ( T d ) of TKX-50 with increasing pressure ( P ) ( T d = 6.28 P 2 + 12.94 P + 493.33, T d and P in K and GPa, respectively, and R 2 = 0.995) and the decomposition under various pressures initiated by an intermolecular H-transfer reaction (a bimolecular reaction). Surprisingly, this finding is contrary to a general observation about the pressure effect on the decomposition of common energetic materials (EMs) composed of neutral molecules: increasing pressure will impede the decomposition if it starts from a bimolecular reaction. Our results also demonstrate that increasing pressure impedes the H-transfer via the enhanced long-range electrostatic repulsion of H + δ ⋯H + δ of neighboring NH3 OH +, with blue shifts of the intermolecular H-bonds. And the subsequent decomposition of the H-transferred intermediates is also suppressed, because the decomposition proceeds from a bimolecular reaction to a unimolecular one, which is generally prevented by compression. These two factors are the basic root for which the decomposition retarded with increasing pressure of TKX-50. Therefore, our finding breaks through the previously proposed concept that, for the condensed materials, increasing pressure will accelerate the thermal decomposition initiated by bimolecular reactions, and reveals a distinct mechanism of the pressure effect on thermal decomposition. That is to say, increasing pressure does not always promote the condensed material decay initiated through bimolecular reactions. Moreover, such a mechanism may be feasible to other EISs due to the similar intermolecular interactions.